Diversification at the narrow sea-land interface in the Caribbean: phylogeography of endemic supralittoral Ligia isopods - Santamaria, Carlos A.; Mateos, Mariana; Hurtado, Luis A. (Frontiers in Ecology and Evolution, 2014)
Phylogeographic studies have provided valuable insights into the evolutionary histories and biodiversity of different groups in the Caribbean, a region that harbors exceptional terrestrial and marine biodiversity. Herein, we examined phylogeographic patterns of the poorly dispersing supralittoral isopod Ligia sampled from 35 localities in the Caribbean Sea and adjacent areas, as well as from Veracruz (Gulf of Mexico), the type locality of L. baudiniana (the only currently recognized native Ligia species in the Caribbean). We conducted Maximum Likelihood and Bayesian phylogenetic analyses of four mitochondrial genes (Cytb, 16S rDNA, 12S rDNA and COI) and Parsimony analyses of one nuclear gene (NaK). We found a well-supported and highly divergent clade of Ligia that is distributed in the Caribbean Sea, Bahamas, southern Florida, Bermuda, and the Pacific coast of Central America and Colombia, but not in the Gulf of Mexico. A characteristic appendix masculina distinguishes this clade from other lineages of Ligia. Large divergences within this clade suggest that it constitutes a cryptic species complex. Genetically and morphologically, the specimens from the type locality of L. baudiniana were indistinguishable from the non-native species L. exotica. Some phylogeographic patterns of Ligia in the study area may be consistent with the proto-Antillean or GAARlandia vicariant hypotheses, but uncertainty concerning divergence times and aspects of the geological history precludes stronger biogeographical inferences. Passive overwater dispersal appears to have played an important role in shaping phylogeographic patterns of Ligia in the Caribbean Sea. These patterns, however, do not correspond with predicted biogeographic patterns based on population connectivity of marine organisms with larval dispersal, and do not reflect the southeast to northwest colonization pattern that has been proposed for the colonization of the Caribbean from South America by some terrestrial animals.